Astronomical Archives in India - S.M. Razaullah Ansari (Journal of Astronomical Data, 2004)
A brief overview is given of the activities of nine observatories (lo- cated at Madras, Lucknow, Trivandrum, Poona, Calcutta, Dehra Dun, Kodaikanal, and Hyderabad) which were established in In- dia in the 19th century. A bibliography of publications of these observatories, sorted according to type of astronomical data, and some notes on observational material, is also presented